On some Pre-Cambrian Metadolerites from the Central Ivigtut Region SW Greenland. - Bondesen, Erling; Henriksen, Niels (Meddelelser om Grønland, 1965)
After their consolidation, the Ketilidian gneisses were transversed by several generations of tensional, doleritic dykes-the Kuanitic dykes. During a later episode (the Sanerutian) these dykes were metamorphosed to varying degrees of alteration which increase in the described area from west to east. Along a specific metadolerite, which can be traced approx. 40 km, the metamorphic grade changes from greenschist to amphibolite facies. In the western parts static conditions and in the eastern parts dynamic conditions, prevailed during the alteration. Sanerutian shear zones in the eastern parts depict the dynamic conditions found here.